RESEARCH TRENDS IN THE HUMANITIES: AN ANALYSIS OF MASTER’S THESES AT THE INTERNATIONAL ISLAMIC UNIVERSITY MALAYSIA - Abdoulaye, Kaba (Malaysian Journal of Library and Information Science, 2004)
Thesis is a key indicator for academic achievement. Analysing and studying theses assist in assessing and evaluating the quality of students’ researches, as well as productivity level of supervisors and their departments. It also helps in identifying research trends and monitoring research activities. This study analyses master’s theses in the Humanities submitted to the International Islamic University Malaysia (IIUM) from 1991 to 1999. A compilation of master’s theses abstract was used as the source of information. A total of 308 theses were analyzed in terms of departmental and geographical affiliation, periodical growth, supervisors’ contributions, and major subject area. The amount of theses grew by 266.7 per cent with greater emphasis on religion and philosophy. The number of supervisors also increased from 35 during 1991-95 to 94 during 1996-99, indicating an increase rate of 168.6 per cent from one period to another. Results of the analyses help identify research trends in the Humanities that have been developed during the 9-year period.